O folheto no cenário das adaptações literárias: releituras do conto chapeuzinho vermelho - Souza, Irany André Lima de (2018)
Born of popular oral narratives, the most well-known fairy tales/ marvels have come to us by the generation to generation propagation promoted by storytellers, and have long been gaining numerous adaptations since their first compilation in book. Among the different re-readings for the different media, the one that called us attention was the Booklet Literature, which maintains a strong relationship with children's stories, because they preserve some characteristics in common. In three chapters, we discuss in this dissertation, successively, the intersections between the booklet and the Children's Literature, about the historical phenomenon of literary adaptation and what place the booklet occupies in that context. In addition, we selected the popular short story Little Red Riding Hood in adaptations for leaflets published in the 21st century as the main corpus of our analysis. In this sense, our research relies on the materiality and textuality of these adaptations, in order to perceive what these texts maintain or alter from the classic tale, with the versions of Perrault and the Grimm brothers as main hypotexts. To this end, we have used qualitative and interpretative research on the booklets The Marriage of Little Red Riding Hood (2006), by Costa Senna, Little Red Riding Hood (2009) by Evaristo Geraldo da Silva, Little Red Riding Hood (2010) by Manoel Monteiro and The Wedding of Little Red Riding Hood (2010) by Cleusa Santo. From the titles, it is noticeable the indication for a new form in which the text will be presented, which already presupposes significant changes for the text wrapped in the specificities of the leaflet. There is even a certain tendency toward moralism in adaptations, as a resurrection of one of the characteristics present in the tales of the Grimm brothers. More than that, there are changes that needed to be analyzed, such as the new configuration of the verbal text in dialogue with the illustrations, which entails new meanings for reading the traditional Little Red Riding Hood story. In order to base our discussion, we used the following basic bibliography: Abreu (1999, 2004, 2006), Ayala (1988, 2016), Burke (2010), Cascudo (1955, 1984), Darnton (1998), and Zumthor (1997, 2007). In this paper, we present the results of the study.